Multiband Rabi antenna using nest microstrip add-drop filter (NMADF) for relativistic sensing applications - Somchat Sonasang; M. Jamsai; M.A. Jalil; Nhat Truong Pham; K. Ray; Niwat Angkawisittpan; Preecha Yupapin; Sarawoot Boonkirdram; Martha Alicia Palomino-Ovando; Miller Toledo-Solano; Khashayar Misaghian; J.E. Lugo (Heliyon, 2023)
A microstrip circuit is designed, constructed, and tested based on the nest microstrip add-drop filters (NMADF). The multi-level system oscillation is generated by the wave-particle behaviors of AC driven along the microstrip ring circular path. The continuous successive filtering is applied via the device input port. The higher-order harmonic oscillations can be filtered, from which the two-level system known as a Rabi oscillation is achieved. The outside microstrip ring energy is coupled to the inside rings, from which the multiband Rabi oscillations can be formed within the inner rings. The resonant Rabi frequencies can be applied for multi-sensing probes. The relationship between electron density and Rabi oscillation frequency of each microstrip ring output can be obtained and used for multi-sensing probe applications. The relativistic sensing probe can be obtained by the warp speed electron distribution at the resonant Rabi frequency respecting the resonant ring radii. These are available for relativistic sensing probe usage. The obtained experimental results have shown that there are 3-center Rabi frequencies obtained, which can be used for 3-sensing probes simultaneously. The sensing probe speeds of 1.1c, 1.4c, and 1.5c are obtained using the microstrip ring radii of 14.20, 20.12, and 34.49 mm, respectively. The best sensor sensitivity of 1.30 ms is achieved. The relativistic sensing platform can be used for many applications.